HARDWARE IN THE LOOP EXPERIMENTAL ASSESSMENT OF P&O AND IC STATEFLOW PV MPPTS (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2022)
This paper deals with the development of the stateflow perturb and observe (P&O) and incremental conductance (IC) maximum power point tracking (MPPT) controllers. The photovoltaic (PV) power system is composed of PV module BP-SX150S powering a resistive load via a dc-dc boost converter controlled using the proposed stateflow models. The proposed stateflow MPPT controllers have been tested and validated in simulation as well as in experimental mode using different test scenarios including PV characteristics, variation in insolation, variation in temperature and variation in duty cycle step. Simulation obtained results show that both proposed stateflow P&O and IC MPPT models track effectively the maximum output power regarding all considered scenarios tests with the best performance for the variable step size versions. Experimental results obtained using the STM32F4 board in the processor in the loop mode confirm the obtained simulations results.
Keywords: Photovoltaic; Maximum power point tracking; Perturb and observe; Incremental conductance